2016
DOI: 10.1159/000448038
|View full text |Cite
|
Sign up to set email alerts
|

MCPIP-1, Alias Regnase-1, Controls Epithelial Inflammation by Posttranscriptional Regulation of IL-8 Production

Abstract: Pattern recognition receptors are critical for the detection of invading microorganisms. They activate multiple pathways that lead to the induction of proinflammatory responses and pathogen clearance. The intensity and duration of this immune reaction must be tightly controlled spatially and temporally in every tissue by different negative regulators. We hypothesized that monocyte chemoattractant protein-1-induced protein-1 (MCPIP-1) might play a role in maintaining immune homeostasis in the epithelium both un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 44 publications
(56 reference statements)
2
37
0
Order By: Relevance
“…Our study demonstrated that the secretion of proangiogenic factors is controlled by the RNase activity of MCPIP1, and MCPIP1 overexpression decreases the level of proangiogenic factors. It is in concordance with previous findings showing that MCPIP1 regulates the level of IL6 and IL8 transcripts by binding to stem-loop structures present in 3 0 UTRs (13,39). VEGF expression is induced by HIF (hypoxia-inducible factors), and we have previously demonstrated that MCPIP1 overexpression reduces the level of HIFs and transcripts for VEGF (25).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our study demonstrated that the secretion of proangiogenic factors is controlled by the RNase activity of MCPIP1, and MCPIP1 overexpression decreases the level of proangiogenic factors. It is in concordance with previous findings showing that MCPIP1 regulates the level of IL6 and IL8 transcripts by binding to stem-loop structures present in 3 0 UTRs (13,39). VEGF expression is induced by HIF (hypoxia-inducible factors), and we have previously demonstrated that MCPIP1 overexpression reduces the level of HIFs and transcripts for VEGF (25).…”
Section: Discussionsupporting
confidence: 93%
“…7), indicating the role of MCPIP1 in acquiring the mesenchymal phenotype of ccRCC cells. It was previously shown that IL1, IL6, and IL8 induce tumor cell migration, invasion, and epithelial-mesenchymal transition and MCPIP1 regulating half time of IL6 and IL1, IL8 transcripts, controlling the level of transcription factors (NFkB, C/EBPb) and signaling proteins (JNK, Akt) may influence on the appearance of EMT signs (13,16,17,39).…”
Section: Discussionmentioning
confidence: 99%
“…4G), supporting the idea that Regnase-1 constitutively degrades IkB-z mRNA. The mRNA stabilizing effect of CHX is consistent with results from earlier studies that have shown that CHX treatment increases IkB-z and CXCL8 mRNA (62,63), both of which have been reported to be degraded by Regnase-1 (39,64). We showed that CHX-induced accumulation of IkB-z mRNA was not enhanced by combined stimulation with IL-17 ( Fig.…”
Section: The Tyk2-stat3 Pathway Mediates Il-17-unrelated Constitutivesupporting
confidence: 91%
“…The fact that these transcripts are strongly upregulated may result from the diminished level of MCPIP1. For example, IL-8 was shown to be a direct target of MCPIP1 [46] while TNFa, COX-2, and BCL-2 levels depend on activity of NF-kB [20,35,47]. It is worth mentioning that Lewis and Spandau found that UVB-induced NF-kB activation did not follow the canonical pathway dependent on IkBa, and the activation of this transcription factor depends on the wavelength and dose used [48].…”
Section: Discussionmentioning
confidence: 99%